Modelos de crescimento sob restrições externas: uma abordagem à la Thirlwall para o Mercosul - Lezcano, Johana Martinez (2012)
This dissertation aims to analyze the long-term economic growth of member countries of Mercosur, making use of the Keynesian approach to growth under external constraint. In this context, we seek to test, empirically, the validity of Thirlwall's Law, in traditional and extended formulations, to Argentina, Brazil, Paraguay and Uruguay, between 1980-2008. Were employed econometric techniques of cointegration, in order to measure the income and price elasticities of demand for imports of these economies, individually. Furthermore, statistical tests were used to compare estimates of product to actual data. Thus, we intend to provide a better understanding of the role of restrictions arising from the Balance of Payments, on the long-term trajectory of growth of nations of the bloc. The results indicate the validity of Thirlwall s Law, over the period analyzed, arguing that the growth of the economies in question was restricted by the balance of the external sector.